ANALISIS PENGARUH RELATIONSHIP QUALITY TERHADAP LOYALITAS PELANGGAN PADA BAGIAN SERVICE SEPEDA MOTOR PT. YAMAHA MATARAM SAKTI MUARA BUNGO - Harahap, Delila Fitri (Jurnal Ekobistek, 2016)
The study aims to determine the effect review of the level of influence that is significant relationship quality (Quality Relations) on Customer Loyalty On Motorcycle Parts Service PT. Yamaha Mataram Sakti Muara Bungo. Populations of 4,512 Consumer Research With slovin using the formula, then the sample That amounted used 98 consumers. The sampling technique using purposive sampling method. Based on the findings from the analysis and discussion that the respondent differences Assessment Quality Relationship variables including good Category And variables including Category loyal customer loyalty. Results of simple linear regression analysis is Y = 4,357 + 0,632X + e. Results t-hitung> t-table (8,219> 1,985) and a significant value 0.000 <0.05 then H0 is rejected its means have positive and significant influence Between The relatioship Quality to Customer Loyalty. The Research Can concluded that the significant positive effect relatioship Quality And Customer Loyalty On motorcycle service section In PT. Yamaha Mataram Sakti Muara Bungo. Based on the calculation results output R2 (R Square) of 0691 Or (69.1%) means that the quality relatioship 69.1% Against influence customer loyalty, while the remaining 30.9% influenced by other variables not examined Posted Or Operation Model Research initials. Keywords: Relationship Quality, Customer Loyalty